Skema Aktan dan Model Fungsional Video Youtube “Pangeran Ikan” sebagai Bahan Ajar Menulis Cerita Fantasi Kelas VII SMP - Salma Dian Rhamadhan; Mukh Doyin (Paedagogie, 2026)
This research is motivated by the persistent obstacles in teaching fantasy story writing at the junior high school level, particularly in understanding narrative structure and developing a coherent storyline. Teaching fantasy story writing requires teaching materials that can help students understand the elements of story building concretely and systematically. This study aims to describe the narrative structure in the video "Prince of the Fish" on the YouTube channel Indonesia Fairy Tales based on the actan scheme and Greimas' functional model and assess its suitability as teaching material for writing fantasy stories for seventh-grade junior high school students. This study uses a qualitative descriptive approach with content analysis. The research data in the form of narratives, dialogues, and events in the video were collected through documentation techniques by listening, transcribing, and noting important parts of the story. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results show that the story "Prince of the Fish" has a complete actantial structure including subject, object, sender, recipient, helper, and opponent. In addition, the functional model of the story develops systematically through the stages of the initial situation, transformation, and final situation. Based on linguistic, psychological, and cultural aspects, this story is considered suitable for use as teaching material for writing fantasy stories for seventh grade junior high school students.